Effective treatment of U(1) gauge field and charged particles in axion inflation. Issue 9 (1st September 2022) - Fujita, Tomohiro; Kume, Jun'ya; Mukaida, Kyohei; Tada, Yuichiro
Abstract: The axionic inflaton with the Chern-Simons coupling may generate U(1) gauge fields and charged particles simultaneously. In order to incorporate the backreaction from the charged particles on the gauge fields, we develop a procedure to obtain an equilibrium solution for the gauge fields by treating the induced current as effective electric and magnetic conductivities. Introducing mean field approximation, and numerically solving self-consistency equations, we find that the gauge field amplitudes are drastically suppressed. Interestingly, as the production becomes more efficient, the charged particles gain a larger part of the transferred energy from the inflaton and eventually dominate it. Our formalism offers a basis to connect this class of inflationary models to a rich phenomenology such as baryogenesis and magnetogenesis.